A Study of English Language Learning Beliefs, Strategies, and English Academic Achievement of the ESP Students of STIENAS Samarinda - Hayati, Noor (IAIN Samarinda, 2015)
Abstract:This research aimed to investigate; students’ English academic achievement, beliefs about English language learning, English language learning strategies, and the relationship of them.Descriptive and correlational design, quantitative methods were applied in this research. The students’ final English scores of the first year, BALLI, and SILL were used as the instruments. The samples of this research were sixty six-first year students majoring Management at STIENAS Samarinda. The data of the research were analyzed using descriptive statistic, multivariate correlation, and Pearson Product Moment correlation.The students’ beliefs about motivation and expectation were the most beliefs held by the students (M=3,65) followed by the nature of language learning (M=3,35), foreign language aptitude (M=2,97), learning and communication strategy (M=2,86), and the difficulty of language learning (M=2,74) . The most preferred strategy used by the students was metacognitive (M=3,35) followed by memory (M=3,28), cognitive (M=3,28), affective (M=3,24), social (M=3,28), and compensation (M=3,18). There was a positive and weak correlation of beliefs and strategies with students’ English academic achievement (R .035). Positive and insignificant correlation was found between English academic achievement and beliefs about English language learning (r = .145, p 0.245 > 0.05) and negative and significant correlation between English language learning strategies and English academic achievement (r = -.144, p 0,248 > 0.05).